Nitrogen vacancy enhanced photocatalytic selective oxidation of benzyl alcohol in g-C3N4. (3rd November 2021) - Bao, Xiaolei; Lv, Xingshuai; Wang, Zeyan; Wang, Minrui; Liu, Mu; Dai, Dujuan; Zheng, Liren; Zheng, Zhaoke; Cheng, Hefeng; Wang, Peng; Liu, Yuanyuan; Dai, Ying; et al.
Abstract: Efficient photocatalytic selective conversion of organic under mild condition remains challengeable for green chemistry. In this work, we determined that nitrogen vacancies (NVs) in graphitic carbon nitride (g-C3 N4 ) could enhance photocatalytic selective oxidation of benzyl alcohol to benzaldehyde. The as-prepared N-deficient g-C3 N4 samples (CNx ) exhibited superior conversion efficiency and excellent product selectivity than pristine g-C3 N4 upon visible light irradiation. By combining experimental characterizations and density functional theory calculations, the NVs in g-C3 N4 could significantly boost carrier separation and act as specific sites to enhance the adsorption and activation of reactants. Thus, our work could provide insight into the pathways of reaction between defects and reactants, and point out a feasible strategy for green fine chemical production. Graphical abstract: The N-deficient g-C3 N4 samples exhibit more superior conversion efficiency and excellent product selectivity than pristine g-C3 N4 during the selective oxidation from benzyl alcohol to benzaldehyde. Image 1 Highlights: The N-deficient g-C3 N4 exhibits higher conversion efficiency and selectivity. The enhanced mechanism is elaborated based on theoretical and experimental results. The NVs can promote the adsorption and activation of reaction substrates. A facile and effective strategy for selective oxidation of alcohols over g-C3 N4 .